Biomedical device for spasticity quantification based on the velocity dependence of the stretch reflex threshold - Ferreira, João Amaro Oliveira (2011)
Spasticity is a common and complex motor disorder that affects more than 12 million persons in the world. There are several studies on spasticity quantification in the literature but there is still a need for measurement improvements. This paper presents the validation, in clinical environment, of a mechatronic medical device, dedicated, and specially designed and constructed for spasticity quantification, in joint of ankle, elbow and knees. This approach is based on the velocity-dependent of the Stretch Reflex threshold. The relevant variables, the measurement range and the adequate measurement systems are indicated. The reliability of the developed mechatronic medical system is confirmed by data acquisition and analysis, following a systematic methodology, also presented in the paper.